Educator Concepts and Competencies from Imam Al-Ghazali's Perspective: Study of the Book of Ihya 'Ulumuddin and Minhajul Muta'alim and their Relevance to Contemporary Islamic Education - Rama Danti, Regilita; Syafe'i, Imam; Sagala, Rumadani (CV. Creative Tugu Pena, 2024)
Educators are a very important factor in education. Because educators are the key in the classroom because they are tasked with leading and directing students' learning activities. Imam Al-Ghazali has sharp opinions, depth and wisdom of thinking and far-reaching views regarding teaching issues and other problems related to it. From the books he wrote, namely the Ihya' Ulumiddin and Minhajul Muta'allim books, we can see the importance of the concepts given by Imam Al-Ghazali in discussing the concept of an educator, which includes definition, position, professionalism/competence and the characteristics of an educator. which is then linked to its relevance in contemporary Islamic education. Because contemporary Islamic education is an activity carried out in a planned and systematic manner to develop students' potential based on the rules of the Islamic religion today. Taking this into account, this research is a library research by examining various literature related to the concept of educators and teacher competence from Imam Al-Ghazali's perspective and its relevance in contemporary Islamic education. By using content analysis techniques in processing primary and secondary data which became the reference for this research, several educational competencies and educational concepts from Imam Al-Ghazali's perspective were found. These competencies are in the form of pedagogical competence, personality competence, social competence and professional competence. And then the concept of Imam Al-Ghazali's Perspective Educator Keywords: Contemporary Islamic Education, Educator Competencies, Educator Concepts